Moderasi Beragama Antara Umat Muslim dan Kristen di Desa Sigara-Gara Kecamatan Patumbak - Muhammad Alvridho Prayoga; M. Ikhsan Ramadhan; Sabda Hafiz Fakar; Rahmad Daim Harahap; Abdul Ghaffar (Medan Resource Center, 2021)
With its diversity, the Indonesian nation is a society with a diverse range of cultures. Culture, religion, race, language, ethnicity, tradition, and other factors all contribute to diversity. Tensions and conflicts between religious groups are common in such a multi-religious community, and they have an impact on life's peace. In order to achieve the Indonesian nation's peace, religion must be moderated in its diversity. They promote mutual knowledge and awareness of religion in terms of appreciating diversity, pluralism, and a readiness to deal equitably with everyone in social situations. An attitude is required in the form of acknowledging the other party's existence, being tolerant, respecting differences of opinion, and not imposing one's will through violence. The government, community leaders, and religious educators must work together to socialize and promote religious moderation in the community in order to achieve harmony and peace, especially in Sigara-Gara Village, Patumbak District, North Sumatra. The method used is library research.